2016
DOI: 10.1177/1359105316628736
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychosomatic health symptoms and common mental illness in Ghanaian adolescents: Age and gender as potential moderators

Abstract: Little is known about the role of age and gender in the association between psychosomatic symptoms and common mental illness (CMI) in Ghanaian adolescents. This cross-sectional study examined age and gender as moderators between psychosomatic symptoms and CMI using data from a school-based survey (N = 770). Males reported higher psychosomatic symptoms and CMI while younger adolescents reported higher CMI only. Psychosomatic symptoms were positively associated with CMI but age and gender did not moderate this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Prevalence in mental distress was relatively high which is consistent with previous studies that found a prevalence of 18.1%, 16.6% and 23% for loneliness, feeling worried and suicidal ideation respectively [ 42 ]. These findings are similar to other reported prevalence rates in Africa [ 4 , 5 ] and the rest of the world [ 2 , 43 , 44 ]. These similarities in prevalence of mental distress in the present sample and in samples across Africa and the rest of the world confirms that mental health problems have become a common life experience of young people globally [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Prevalence in mental distress was relatively high which is consistent with previous studies that found a prevalence of 18.1%, 16.6% and 23% for loneliness, feeling worried and suicidal ideation respectively [ 42 ]. These findings are similar to other reported prevalence rates in Africa [ 4 , 5 ] and the rest of the world [ 2 , 43 , 44 ]. These similarities in prevalence of mental distress in the present sample and in samples across Africa and the rest of the world confirms that mental health problems have become a common life experience of young people globally [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although there is a paucity of research studies on adolescent mental health in Africa [ 3 ], a few studies conducted in Africa found that 1 out of 7 children have significant mental health problems and 1 out of 10 were diagnosed with a mental health problem [ 4 ]. Quite recently, about 62% of Ghanaian youth have reported having moderate to high common mental illnesses [ 5 ]. This evidence is in consonance with what is already known that mental health problems are a leading cause of disease burden globally including both low-and middle-income economies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these challenges is engagement in risky behaviours (e.g., having unprotected sex and substance use, self-harm etc.) which increases their vulnerability to poor physical and mental health outcomes ( Glozah & Pevalin, 2016 ; Patel, Flisher, Hetrick & McGorry, 2007 ; WHO, 2014a ). Since it has been estimated that sub-Saharan Africa will have more adolescents than any other region by the year 2050, adolescent health research and interventions, thus become key priority ( WHO, 2014a ).…”
Section: Introductionmentioning
confidence: 99%
“…Students who experience the degree had obstacles in completing the thesis, so that they were not directly able to achieve academic success. Psychosomatic symptoms described the condition of mental strength possessed by students was still low, because psychosomatic symptoms are positively correlated with mental strength a person has (Glozah & Pevalin, 2017). That is, mental strength contributes indirectly to students' academic success.…”
Section: Introductionmentioning
confidence: 99%